Pengaruh Tax Planning, Ukuran Perusahaan, CSR, Terhadap Manajemen Laba - admin, admin; Haninun, Haninun (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
Various financial management policies are crucial in ensuring the sustained operations of a firm, as evidenced by the substantial profits made by the organization. The occurrence of income management was seen at PT Bank Mandiri Tbk. According to the BPK, the impact of the state losses was deemed atypical. Organizations that engage in corporate social responsibility (CSR) initiatives and effectively convey them through their financial reports stand to gain advantages in terms of cultivating a favorable public perception and garnering investor confidence. There are several factors that may lead management to engage in the manipulation of financial reporting, including tax planning and the size of the organization. Profitable corporations have the ability to entice investors to allocate funds towards their stocks, so enabling these organizations to leverage their financial gains by means of earnings management. The sample utilized in this research involves the implementation of purposive sampling., while the analysis of the quantitative data is conducted through the utilization of multiple linear regressionThe results of the investigation suggest that within the banking sector, A positive correlation that is statistically significant is evident between earnings management and factors such as tax planning, firm size, and corporate social responsibility (CSR).